3D-numerical predictions of flow structure and heat transfer behavior in heat exchanger tubes inserted with different patterns of double-V baffles - Amnart Boonloi; Withada Jedsadaratanachai (Case Studies in Thermal Engineering, 2022)
3D-simulation of convective heat transfer and laminar flows at an isothermal wall of a circular tube heat exchanger (CTHE) inserted with different configurations of double-V baffles (DVB) are presented. The insertion of DVB is done with the objective to produce vortex flows and impinging flows to perturb the thermal boundary layer (TBL) over the isothermal wall, thus increasing convective heat transfer coefficient and efficiency. Various DVB parameters which contribute to the best thermal efficiency are considered. Effects of six DVB shapes (Type A-F), DVB height (b/D = 0.05–0.30) and flow directions (+x, -x) on air stream and thermal mechanisms with Reynolds number within 100–2000 (calculated with the inlet condition) are compared. Simulation results of flow structure (streamline structures in transverse planes) and heat transfer characteristics (fluid temperature distributions and local Nusselt number (Nux) contours) are reported. Insights into the flow pattern and heat transfer are key to improve heating and cooling system performance. The improvement of the CTHE inserted with the DVB is presented in terms of the Nusselt number (Nu) and the thermal enhancement factor (TEF), while the pressure loss is presented by the friction factor (f). Simulation results show that the DVB creates vortex and impinging flow over the surface of the circular tubes in the CTHE of all investigated tests. The best TEF and the best Nusselt number ratio are 3.55 and 22.42, respectively.
Keywords: Heat Transfer Mechanisms; Heat Transfer and Optimization; Nanofluid Flow and Heat Transfer